Examining the therapeutic alliance: a case study at a drug rehabilitation facility - Isa Amat M.; Mohd Sukor N.; Ku Johari K.S.; Mohd Najib N. (Hampstead Psychological Associates, 2024)
Indexed by SCOPUS/ERA